The contribution of human papilloma virus infection to cutaneous squamous cell carcinoma in patients with chronic lymphocytic leukemia. Issue 2 (4th March 2021) - Bhavsar‐Bhakta, Preeya; Hamza, Mugahed; Mehravaran, Sepideh; Krishnan, Bhuvaneswari; He, Qin; Tyring, Steven; Rady, Peter; Rivero, Gustavo; Cohen, Daniel N.; Sosa, Iberia Romina
Abstract: Patients with chronic lymphocytic leukemia (CLL), a B‐cell malignancy characterized by impaired humoral and cellular immunity, are at increased risk of developing cutaneous squamous cell carcinoma (cSCC). Human papilloma virus (HPV) is the most common sexually transmitted infection worldwide and it has been associated with various malignancies, including cSCC. Impaired cell‐mediated immunity is considered a primary risk factor in HPV‐induced cSCC. We examined cSCC lesions from CLL patients with consensus review and HPV genetic analysis to further characterize the relationship between HPV and prevalence of cutaneous malignancy in this population. Eleven patients with CLL contributed 35 cSCCs. Treatment with chemotherapy shortened the latency time to first cSCC. HPV was detected in 54% of the lesions. Among the HPV‐positive cSCC lesions, 84% of the lesions contained alpha‐genus HPV, 42% contained beta‐genus HPV, and 26% of the lesions contained both genera. There was a significant association between HPV‐containing lesions and peritumoral lymphocytic inflammation, suggesting this as a future area for further characterization. The majority of the lesions, including those with alpha‐genus HPV, occurred in sun‐exposed areas, such as the scalp and face. These findings may lead to practice‐changing recommendations for skin cancer, including the use of vaccinations to reduce HPV‐associated skin cancer.